Exploring intercultural competence among students in Malaysian campuses - Syarizan Dalib,; Minah Harun,; Norhafezah Yusof,; Mohd Khairie Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Much has been written about intercultural competence in the academic literature, yet our present knowledge of the subject matter was vastly drawn from the most prominent views of the Western scholars. Accordingly, many calls have been made to reconsider the predominantly defined concept in different cultural contexts, particularly in the Southeast Asia region such as Malaysia. Therefore, this study aims to explore how the local undergraduate students of various ethnicities reflect on their everyday experience within the context of Malaysian campuses. In this study, the pyramid model of intercultural competence developed by Deardorff in 2006 is used to examine the students’ experiences with their foreign friends and their sensemaking of intercultural competence. Data were collected from in-depth interviews with selected undergraduate students from three universities in the Northern part of Peninsular Malaysia. The research identified two important themes: establishing connection and developing communicative skills. The findings contribute into re-consideration of Deardorff’s model. While the model emphasizes more on psychological factors, the findings indicate that language proficiency is viewed as an important factor in the process of interaction between local students and their foreign counterparts. The implication of this study highlights the idea that students’ ability to develop language and communication skills will allow them to be more intercultural competent. This study adds Malaysian perspective to the current understanding of intercultural competence.